STATUS HUBUNGAN HUKUM OJEK DARING DENGAN PERUSAHAAN JASA TRANSPORTASI DI ERA GIG ECONOMY DITINJAU DARI PERMENHUB NOMOR 12 TAHUN 2019 - Akbar, Sachril; Hikmawati, Elok; Nurhayani, Nurhayani (Lex Jurnalica, 2025)
ABSTRACTThis research focuses on an in-depth analysis of the unique legal relationship between online motorcycle taxi drivers and transportation service providers in the context of the gig economy. In the increasingly dominant digital era, app-based business models have revolutionized the way we work, including in the transportation sector. Ministerial Regulation Number 12 of 2019 serves as a relevant legal basis for examining this employment relationship, particularly regarding the employment status of drivers. The aim of this research is to determine how the legal status of online motorcycle taxi drivers compares between Ministerial Regulation Number 12 of 2019 and Law Number 13 of 2003 on Manpower and how legal protection is provided for the status of online motorcycle taxi drivers in carrying out cooperative work relationships with application companies. This research uses a normative juridical method (Legal Research) with a conceptual approach because there are no existing legal rules for the problems faced. Using a qualitative approach, it is hoped that the complex dynamics occurring in digital platforms can be revealed, ranging from daily work mechanisms to their impact on the welfare of drivers. The results of the research show that Ministerial Regulation No. 12 of 2019 offers high flexibility but provides insufficient legal protection for online motorcycle taxi drivers, while the Manpower Law provides stronger protection but is less flexible to technological developments. Legal protection for online motorcycle taxi drivers is still complex and many drivers feel unprotected despite the existence of Ministerial Regulation No. 12/2019. A fair solution requires cooperation between the government, companies, labor unions, and academicsKeywords: Legal relationship; Online motorcycle taxi drivers; Transportation service companies; Gig economy; partners. ABSTRAKPenelitian ini berfokus pada analisis mendalam mengenai hubungan hukum yang unik antara pengemudi ojek daring dan perusahaan penyedia jasa transportasi dalam konteks ekonomi gig. Dalam era digital yang kian mendominasi, model bisnis berbasis aplikasi telah merevolusi cara kita bekerja, termasuk dalam sektor transportasi. Peraturan Menteri Perhubungan Nomor 12 Tahun 2019 menjadi landasan hukum yang relevan untuk mengkaji hubungan kerja ini, khususnya dalam hal status kepegawaian pengemudi. Tujuan dari penelitian ini untuk mengetahui bagaimana perbandingan status hubungan hukum ojek daring antara Peraturan Menteri Perhubungan nomor 12 tahun 2019 dengan Undang-undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan dan bagaimana perlindungan hukum terhadap status pengemudi ojek daring dalam pelaksanaan hubungan kerja sama dengan perusahaan aplikasi. Dalam penelitian ini menggunakan metode yuridis normatif (Legal Research) dengan menggunakan pendekatan konseptual karena belum atau tidak ada aturan hukum untuk masalah yang dihadapi. Dengan menggunakan pendekatan kualitatif, diharapkan dapat terungkap dinamika kompleks yang terjadi dalam platform digital, mulai dari mekanisme kerja sehari-hari, hingga pengaruhnya terhadap kesejahteraan pengemudi. Hasil dari penelitian menunjukkan bahwa Permenhub No.12 Tahun 2019 menawarkan fleksibilitas tinggi namun kurang memberikan perlindungan hukum bagi pengemudi ojek daring, sementara UU Ketenagakerjaan memberikan perlindungan lebih kuat tetapi kurang fleksibel terhadap perkembangan teknologi. Perlindungan hukum untuk pengemudi ojek daring masih kompleks dan banyak pengemudi merasa tidak terlindungi meskipun ada Permenhub No. 12/2019. Solusi yang adil memerlukan kerja sama antara pemerintah, perusahaan, serikat pekerja, dan akademisi. Kata Kunci : Hubungan hukum; Pengemudi ojek daring; Perusahaan jasa transportasi; Gig economy; mitra.